The Empowering the Al-Ikhsan Women Farming Group through Increasing Local Fruit-Based Functional Drink Products: The Empowering the Al-Ikhsan Women Farming Group through Increasing Local Fruit-Based Functional Drink Products - lubis, Rafiqah amanda (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2025)
Abstract This community service activity aims to empower the Al-Ikhsan Women Farming Group (KWT) in Simatohir Village, Padangsidimpuan Angkola Julu District, through training in processing local fruit into functional drinks of high economic value. The potential of local fruit such as salak, balakka, and haramonting has not been optimally utilized, so this program is designed to improve skills in product innovation, business management, and digital marketing. Implementation methods include socialization, training, mentoring, and evaluation using Focus Group Discussion (FGD). The results of the activity showed a significant increase in participants' knowledge and skills, where 90% of participants understood the training material, 95% were satisfied with processing practices, and 90% were satisfied with the facilities provided. The output produced is in the form of two labeled functional drink variants, an active social media account for promotion, and a distribution permit design (PIRT). This program proves that empowerment based on local potential is effective in increasing the economic independence of village women and is a model for sustainable rural MSME development.